Students' Learning Interests with Audio-Visual Media in PJOK Subjects - Setiawan, Habil Eka (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Increasing interest in something is basically helping students see how the material they are expected to learn relates to themselves as individuals. The use of audio-visual media with liquid crystal display is not used frequently, namely because the learning facilities and infrastructure are not yet complete; there is no liquid crystal display (LCD) in each class; therefore, teachers always develop creativity in using audio-visual learning media. The goal of this study was to determine students' interest in learning with audiovisual media (LCD) in the subject of PJOK. The descriptive quantitative nature of this study stems from its numerical focus and the use of statistical analysis for data management. The study was conducted in class 6 at MI Ma'arif NU Sekaran, totaling 17 students. The results of the study indicated that 13 students who like PJOK learning using audio-visual media (LCD) had a percentage of 76.5%, and only 4 students who do not like PJOK learning using audio-visual media (LCD) had a percentage of 23.5%. Therefore, we conclude that the use of audiovisual media, specifically liquid crystal displays, significantly influences students' interest in learning, particularly in PJOK subjects.